PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK MATEMATIKA BERBASIS HIGHER ORDER THINKING SKILL UNTUK PENGAYAAN DI KELAS IV SEKOLAH DASAR - Azizah, Salma Haya; Irianto, Sony; Bintaro, Tri Yuliansyah (STKIP PGRI Bandar Lampung, 2019)
This study is a research and development which aimed to 1) the assessment of experts toward student worksheet activity mathematic on enriching of statistic based on higher order thinking skill; 2) the students' response toward student activity sheet mathematic on enriching of statistic based on higher order thinking skill. This research and development use through Thiagarajan, Semmel, dan Semmel (1974: 5-9) research and development method of modifications 4-D. Data collection techniques used four stage Define, Design, Develop, Disseminate. This study, the product test used setting Lesson Study divide into three stage plan, do, see. The average score of expert assessment was 3,80 in valid criteria. The average score of student response was 4,32 in very good response, so it could be concluded that student activity sheet mathematic on enriching of statistic based on higher order thinking skill in the fourth grade of elementary school was able to take step and improve higher order thinking skill of students